Phase competition and light-induced ordering in charge density waves - Zong, Alfred; Kogar, Anshul; Gedik, Nuh (SPIE, 2021)
Photoexcitation by an intense laser pulse can alter the free energy landscape of a solid so that it can access states of matter that do not normally exist in thermal equilibrium. Discoveries of such light-induced states are often found in materials that host phase competition, where one state of matter lies in close proximity to another and photoexcitation provides sufficient energy to overcome the barrier between the neighboring phases. Here, we study the rare-earth tritelluride family (RTe3): It possesses two nearly-equivalent and competing charge density waves (CDWs) in equilibrium, out of which one dominates over the other due to a small lattice anisotropy. When both CDWs are present, such as in ErTe3, an optical pulse transiently weakens both orders. If only the dominant CDW exists, such as in LaTe3, this order is suppressed by photoexcitation while the subdominant density wave emerges. The light-induced subdominant CDW is distinct from its equilibrium counterpart. Nonetheless, this light-induced CDW relaxes at the same time when the original CDW is re-established, indicating a strong phase competition between the two in the out-of-equilibrium regime. Our results provide a framework for understanding the interplay between competing orders and for unleashing novel states of matter that are "trapped" under equilibrium conditions.